Profil miskonsepsi pemahaman peserta didik terhadap materi pecahan ditinjau berdasarkan gaya belajar visualization auditory kinesthetic (vak) pada peserta didik kelas v sekolah dasar - Luthfiyah Nanda Bertha Armelia; Riyadi Riyadi; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2022)
Abstract. The purpose of this study is to analyze and describe the profile of misconceptions based on the Visualization, Auditory, Kinesthetic (VAK) learning style regarding students' understanding of fractions and the causes of misconceptions in the fifth grade of SD Negeri Wonosri. This research is a qualitative research method. The research subjects were the fifth grade students of SD Negeri Wonosri. Data collection techniques are learning style tests, fractional material tests, interviews with teachers, and interviews with students. The validity of the data using technical triangulation techniques. Data analysis used descriptive analysis techniques. The research procedure is the initial preparation, the research implementation stage, the data processing stage, and the data presentation.The results showed that two research subjects who had a visualization learning style experienced systematic misconceptions and numeracy misconceptions. Two research subjects who have an auditory learning style experience systematic and translation misconceptions. Two other research subjects have a kinesthetic learning style experiencing systematic misconceptions. Factors causing students to experience misconceptions are preconceptions, lack of understanding of concepts, low interest in learning, teacher teaching methods that are too fast, lack of understanding of steps, students' associative thinking.Key Words: misconception, fraction material, learning style, and elementary school